Cannabis recreativa como oportunidad para exportar desde Colombia (2023)
The global legal cannabis industry has experienced remarkable growth in recent years, currently close to 30 countries have legalized its production, sale and consumption for medicinal purposes, and another five countries have legalized cannabis for recreational use. These countries are Uruguay, Mexico, the United States, Canada and Malta. In Colombia, bill PL-194-19 is being approved, which seeks to legalize the cultivation, production, storage, processing and commercialization of cannabis to protect the population from the risks associated with the illegal trade in psychoactive substances or drug trafficking. .